Letramento em saúde, bem-estar e os comportamentos de prevenção contra a covid-19 de pais e cuidadores de crianças pré-escolares - Sena, Marcela Matias (2024)
Aim: To analyze the level of health literacy, well-being and COVID-19 prevention behaviors of parents and caregivers of preschool children. Methodology: This is an analytical, cross-sectional and quantitative study. The research is a cross-section of a multicenter cluster-randomized study and used baseline data. Data collection took place from November 2022 to May 2023 in early childhood education centers in the states of Paraíba, Ceará and Rio Grande do Norte. The study population was made up of parents and caregivers of children aged 2 to 5 enrolled in the institutions, with a final sample of 732 participants. A sociodemographic and economic questionnaire, a questionnaire on the implications of the COVID-19 pandemic, the World Health Organization's Well-Being Index and the Brazilian Version of the Health Literacy Instrument (HLS-EU-Q6) were applied. The descriptive and statistical analysis of the data was carried out using the Statistical Package for the Social Sciences software. The data was organized in tables with absolute and relative frequencies, means and standard deviations. Data normality was checked using the Kolmogorov-Smirnov test. The association between the predictor variables and the outcome was performed using the Chi-square test and Fisher's test, considering a p value < 0.05, odds ratio with a 95% confidence interval. The binary logistic regression method included variables that presented statistical significance in the bivariate analysis. Results: Most parents and caregivers had inadequate or problematic health literacy (n=629, 90%) and high well- being (n=494, 68%). Adequate literacy was associated with: the higher education of the head of the family (p=0.000; IC:1.62-5.08) and the child's main caregiver criança (p=0.048; IC:1.45-4.96); the adequate child's birth weight (p=0.027; IC:0.19-0.92); social isolation behavior (p=0.042; IC:1.01-3.46); modifying the child’s leisure routine (p=0.026; IC:1.06 -3.02) and screen time (p=0.023; IC:1.07-3.07); and the number of people in the parents' support network during the pandemic (p=0.040; IC:0.21-0.98). High well-being was associated with: high socioeconomic level (p=0.000; IC:2.22- 4.90); the caregiver's ease in guiding the child (p=0.043; IC:1.01-2.57); the absence of maternal complications during pregnancy (p=0.012; IC:1.09-2.08) and the child immediately after birth (p=0.029; IC:1.04-2.57); home visits in the first week of life (p=0.009; IC:1.11-2.10); receiving information from health professionals during consultations (p=0.013; IC:1.09-2.22); the caregiver's concern regarding the pandemic (p=0.035; IC:1.02-2.18); social isolation behavior (p=0.020; IC:0.46-0.93); modifying the mother (p=0.006; IC:1.13-2.14) and child’s (p=0.035; IC:1.02-1.97) sleep routine; the absence of the need for psychological care (p=0.001; IC:1.24-2.50); the presence of a support network during the period (p=0.009; IC:1.15-2.74); changes in living conditions (p=0.014; IC:0.48-0.92); and not worrying about paying the bills (p=0.012; IC:1.09-2.16). Conclusion: Health literacy and well-being are the result of several social determinants and influence disease prevention and health promotion behaviors.